Biochemical Evaluation of Analgesic and Sedative Drug Use and Pain Control Outcomes in Paediatric Surgical Patients - Zia Muhammad, Iqbal Ahmad, Nusrat Ullah Khan, Muhammad Aitmaud Uddolah Khan, Farooq Ahmad Malik, Samia Mehmood (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pain control is a key aspect of pediatrics surgery. Post-operative pain, anxiety and physiological stress levels are routinely reduced through the use of analgesics and sedative drugs. But scarce information exists on their biochemical effects and relation to pain control outcomes after surgeries in paediatric population of Pakistan. Objective: To assess biochemical changes associated with the use of analgesic and sedative drugs and to find the biochemical effects of postoperative pain control in paediatric surgical patients. Methods: This multicenter prospective observational study was conducted at Khyber Teaching Hospital and Khyber Medical College, Peshawar, Pakistan, and DG Khan Medical College, Dera Ghazi Khan, Pakistan, from June 2022 to June 2023. Using consecutive sampling, 120 paediatric patients, aged between 1-12 years undergoing elective or emergency surgical procedure were enrolled. Demographic data, medicine use, biochemical parameters, and postoperative pain outcomes were documented. Before surgery and 24 hours after surgery, serum cortisol, blood glucose, C-reactive protein (CRP), liver function tests (LFT), renal function tests (RFT) and electrolyte profiles were evaluated. Age appropriate validated pain scales were used for the assessment of pain. The data were analyzed statistically using SPSS version (26.0) and P value of < 0.05 was taken as significant. Results: The mean age of the participants is 6.7 ± 3.1 years and there were 60.0% males. The most commonly given analgesic (85.0%) and sedative (65.0%) drugs were Paracetamol and Midazolam, respectively. Mean serum cortisol levels decreased significantly from 19.2 ± 4.5 µg/dL preoperatively to 13.4 ± 3.6 µg/dL postoperatively (p<0.001). Progressively decreasing postoperative pain scores started at 6.3 ± 1.4 at 1 hour and ended at 1.6 ± 0.8 at 24 hours. Patients receiving multimodal analgesia demonstrated significantly lower pain scores and cortisol levels compared with monotherapy recipients (p<0.001). There was no clinically significant liver, renal or electrolyte derangements. Conclusion: Analgesic and sedative drugs were effective in helping to manage postoperative pain and reduce physiological stress responses in paediatric surgical patients. Multimodal analgesic approaches achieved a better biochemical and clinical profile with a safe profile. Keywords: Paediatric Surgery, Analgesics, Sedatives, Pain Management, Cortisol, Postoperative Care.